Benevolent government, managerial incentives, and the virtues of privatization - Christoph Lülfesmann (Fondazione Eni Enrico Mattei (FEEM), 2002)
We show that privatization can be beneficial even if the government is rational and benevolent, and if the firm's economic and informational environment is independent of the governance structure. The model assumes that wage contracts between the firm's owner (government or private entrepreneur) and its manager are incomplete. Managerial incentive schemes are set optimal given this restriction. Nevertheless, the ownership structure feeds back on managerial effort because the initial contract is modified if one party in the relationship has a credible threat to quit or to shut down the firm. In particular, since benevolent government and profit-maximizing entrepreneur have different objective functions, the occurence of renegotiation is regime dependent. Public ownership is optimal if the firm operates under a serious shutdown threat. Conversely, privatization is strictly preferable if the firm's future survival does not crucially depend on the success of managerial effort.
Keywords: D23; H57; L51; 330; Privatization; incomplete contracts; innovative technologies; Privatisierung; Führungskräfte; Unvollständiger Vertrag; Leistungsanreiz; Technischer Fortschritt; Theorie